Inhibition of toxic activities of Bothrops asper venom and other crotalid snake venoms by a novel neutralizing mixture - Borkow, Gadi (1997)
The majority of snake bites in Central America are caused by Bothrops asper, whose venom induce complex local effects such as myonecrosis, edema and especially hemorrhage. These effects are only partially neutralized by the clinically used antivenom, even when administered rapidly after envenomation. Recently we screened 49 substances for antihemorrhagic activity and found that a mixture composed of CaNa2, EDTA, a B. asper serum fraction (natural antidote), and the currently used horse polyvalent antiserum is highly effective in the neutralization of local and systemic hemorrhage developing after B. asper envenomation (Borkow et al., Toxicon 35, 865-877, 1997). In the present study we screened the best six antihemorrhagic compounds for their capacity to neutralize the lethal activity in mice and the proteolytic, hemolytic, and antiattachment activities in vitro of the venom. The compounds tested included the currently used horse antivenom, rabbit antiserum against whole B. asper venom or against heated venom, B. asper and Natrix tessellata serum fractions, and CaNa2 EDTA. The constituents of the antihemorrhagic mixture were also the best inhibitors of the other examined toxic activities. Importantly, the mixture effectively neutralized toxic activities of an additional nine venoms from snakes abundant in Central America. This work suggests that the polyvalent antivenom used in Central America could be enriched with a B. asper serum fraction producing a more effective antivenom. In addition, the local application of CaNa2 EDTA to neutralize hemorrhagic toxins, immediately after a snake bite, may provide rapid inhibition of local damage caused by the venoms.